Exergy analysis, preliminary, of cogeneration from forests plantations - Gomes, Sérgio Inácio; Jorge, Luiz Mário Matos; Paraíso, Paulo Roberto; Conceição, Wagner André dos Santos; Andrade, Cid Marcos Gonçalves (Revista Ciências Exatas, 2009)
The fossil sources will be exhausted in the near future or have their costs prohibitive for use as fuel and to generate electricity. Furthermore, the use of fossil fuels in any form, have been harmful to the environment. In this work we make the exergy analysis, preliminary quantitative, for three alternatives using of energy from forest plantations (wood). The first with the direct conversion of wood energy in power; in the second, half of the wood is used to generate electricity and steam to be used in the process of gasification, with the other half, followed with the generation of electric power in fuel cell; and the third using a cogeneration plant coupled to gasification of wood, and fuel cell. How, in theory, would be expected due to have a priori, less sources of irreversibility, the direct conversion of energy into electric energy from forest plantationswas more favorable from the exergy point of view, and the third is the worst alternative. However, we can not discard the possibility of the use of energy from the forest plantations as a primarysource in fuel cell; this will depend on operational situations where you want to use the energy.Keywords: Forest plantations, Fuel cells, Exergetic Anlysis, Cogeneration, Gasification.